Ennodius und Martial - Adamik, Tamás (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
Magnus Felix Ennodius, the bishop of Ticinum (modern Pavia), died in 521. He has left letters, poems, oratorical pieces, saints’ lives and controversial literature. Ennodius’ writings were composed for specific audiences on particular occasions. His Latinity is very literate, syntactically complex, and difficult to understand. He cultivates the short literary forms: letters, panegyrics, declamatory themes (dictiones), short poems, epithalamium, epigrams, epitaphs, hymns. In the preface of his epithalamium for Maximus, he displays the essential qualities of spring with Martial’s vocabulary. This fact directed my attention to the relation of Ennodius to Martial. Comparing Ennodius’s epigrams with Martial’s, I realized that in his epigrams Ennodius imitated Martial both in topics and expressions.